Influence of synchronized domain visualizations on program comprehension - Oliveira, Nuno (2010)
An effective program comprehension is reached when it is possible to view and relate what happens when the program is executed, synchronized with its effects in the real world concepts. This enables the interconnection of program’s meaning at both problem and program domains. To sustain this statement we need (i) to develop a tool which provides and synchronizes views at both domains, and (ii) to perform an experiment to measure the actual impact of this approach. So, in this working session we aim at discussing the benefits of providing synchronized domain visualizations. We also envisage to discuss the preparation and conduction of appropriate experiments that will test that benefits. A case study will be used and the discussion will be supported by experimental material specially prepared for the occasion, but adapted from material already used in previous experiments.